Peran Ninik Mamak Dalam Pencegahan dan Pengurangan Resiko Penyakit HIV/AIDS pada Remaja di Kota Solok 2019 - Abdul Gafar; Syahrum Syahrum (Poltekkes Kemenkes Padang, 2021)
To inhibit the increase and spread of HIV-AIDS, it is necessary to partnership between civil society, people with HIV-AIDS, government and the role of community leaders. In Minangkabau Ninik Mamak is obliged to educate nephews in the field of religion, customary values, culture in community life to be able to live harmoniously. Data from the Solok City Health Office with HIV-AIDS in 2019 amounted to 54 cases and 30 of them died. The purpose of this study is to find out how Ninik Mamak's role in the application of indigenous and cultural values to the prevention and reduction of the risk of HIV-AIDS disease in adolescents in solok city. This research uses qualitative methodology with a case study approach, data collected through in-depth interviews. The results of the study of most ninik mamak have not played a role in maximally applying and instilling the values of Indigenous and Cultural Minangkabau to the youth nephew about the prevention and reduction of the risk of HIV-AIDS disease. Ninik Mamak as an informal leader who has a close relationship with the nephew must provide motivation, direction, guidance, and teaching wisely and wisely to the nephew to do it in everyday life. Suggestions that Ninik Mamak increase its role and function to instill indigenous values and Minangkabau culture in the daily life of youth nephews as an awareness effort in the prevention and reduction of the risk of HIV-AIDS disease.